Womanpower Unlimited and the Black Freedom Struggle in Mississippi - Morris, Tiyi Makeda (Book collections on Project MUSE., 2015)
"Provides the first comprehensive examination of the Jackson, Mississippi-based women's organization Womanpower Unlimited. Founded in 1961 by Clarie Collins Harvey, the organization was created initially to provide aid to the Freedom Riders, who were unjustly arrested and tortured in the Mississippi jails. Womanpower Unlimited expanded its activism to include programs such as voter registration drives, youth education, and participation in Women Strike for Peace. Womanpower Unlimited proved to be significant not only with regard to civil rights activism in Mississippi, but also as a spearhead movement for revitalizing Black women's social and political activism in the state. This study contributes to our understanding of how the civil rights movement was sustained in Mississippi through grassroots activism, and also foregrounds women's activism as an integral component of this leadership. In this process, Morris engages contemporary theoretical questions about leadership, support work, and gendered activism within the movement while demonstrating a broad human rights agenda"--Provided by publisher.